1997
DOI: 10.1136/qshc.6.4.181
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the relation between research and clinical policy: a study of clinicians' views.

Abstract: Objectives-To describe the relation between research evidence and local obstetric unit policy for specific areas of care and to explore clinicians' views about the reasons for any discrepancies identified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 6 publications
1
15
0
Order By: Relevance
“…However, sophisticated medicine is an art. (Johnson, 2002(Johnson, : 1495 Studies not surprisingly therefore indicate that adoption of guidelines depends very much on local practice, as well as individual disposition (Berrow et al, 1997;Dye et al, 2000;Foy et al, 2001;Templeton et al, 2001). Clinical Governance and Clinical Audit seems likely to be important here in putting them on the agenda in many organisational situations.…”
Section: Operational Governancementioning
confidence: 94%
“…However, sophisticated medicine is an art. (Johnson, 2002(Johnson, : 1495 Studies not surprisingly therefore indicate that adoption of guidelines depends very much on local practice, as well as individual disposition (Berrow et al, 1997;Dye et al, 2000;Foy et al, 2001;Templeton et al, 2001). Clinical Governance and Clinical Audit seems likely to be important here in putting them on the agenda in many organisational situations.…”
Section: Operational Governancementioning
confidence: 94%
“…Rather, it was their awareness of the limitations of research data which made them sceptical. Concerns were expressed about the doubtful validity and uneven quality of some research studies and about the adequacy or relevance of their findings for clinical practice ( Berrow et al . 1997 ).…”
Section: Resultsmentioning
confidence: 99%
“…Ideas and information about barriers to implementation have accrued from a variety of different sources including: theoretical literature on the uptake of innovations within and beyond health care ( Rogers 1983; Williams & Gibson 1990); analyses of the impact of different implementation strategies ( Grimshaw & Russell 1993); studies in which clinicians in various fields were asked what they thought would prevent them applying evidence ( Grol 1992; Mansfield 1995; Dawson 1995; Walsh 1997); and detailed case studies of specific initiatives for changing clinical practice ( Dopson et al . 1994 ; Berrow et al . 1997 ; Wood et al .…”
Section: Introductionmentioning
confidence: 99%
“…Berrow et al reported that divergence of clinical practice from research evidence is often due to concerns about the adequacy and applicability of the research and concerns about the ability of the medical community to enact changes based on evidence. 18 Further investigation into what factors are important for the incorporation of evidence on PSA screening into clinical practice would be illuminating, particularly when the outcomes of clinical trials differ.…”
Section: Discussionmentioning
confidence: 99%